Oral Hygiene Knowledge among Medical and Dental Faculty - Iqbal, Ayesha; Hirani, Suraiya; Hanif, Sarah; Salim, Sandhiya (European Dental Research and Biomaterials Journal, 2020)
Objective Oral health reflects the physical and mental health of the individual as it is the first line of entrance of bacteria into the body. Knowledge regarding oral health is an essential component for dental as well as medical faculty as they are responsible for maintenance of health of the individual in clinical and nonclinical practices. Therefore, the aim of the study was to determine the predominance of oral hygiene with dental brushing, flossing, smoking, usage of mouthwash, and frequency of dental visits.Materials and Methods To achieve the aim of the study, a questionnaire was created to access the awareness of oral hygiene status among medical and dental faculty. The study was conducted at Sir Syed College of Medical Sciences and all the faculty staff from senior faculty to junior staff was included in the study.Results A total of 200 participants participated in the study of which 125 were females (62.5%). The results specify that the female faculty members have a better oral hygiene knowledge as compared with male faculty members. Single faculty members or staff visit a dentist more as compared with married faculty members or staff as single staff has more time and less responsibilities at home. Knowledge regarding oral hygiene care of overall participants is satisfactory.Conclusion In conclusion, the oral health care and knowledge is far better in dental faculty member as compared with medical faculty member as the oral care is the substantial component of the dental core curriculum.
Keywords: oral hygiene; faculty; knowledge